ANALISIS PERLINDUNGAN HUKUM ATAS PENOLAKAN MUTASI OLEH TENAGA KERJA YANG BERAKIBAT PEMUTUSAN HUBUNGAN KERJA OLEH PENGUSAHA (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR: 1467 K/PDT.SUS-PHI/2017) - Jessica Condro; Sugandi Ishak (Jurnal Hukum Adigama, 2020)
An employment relation is an agreement made between a worker/labourer and an enterpeneur and an entrepeneur that specifies work requirements, rights and obligations of the parties. Based on the facts, work relationships do not always go well. One of the problems that often occur is termination of employment due to refusal of mutation. Basically, the purpose of the mutation itself is to increase efficiency and effectiveness of work in the company. However, mutation in some cases is often misused by employers to avoid paying severance pay or the rights of the worker/labourer. For example, a worker who has worked for many years is suddenly transferred to distant places. Hence, raising the question, how is the legal protection for workers who refuse the mutation and result in the termination of employment (related to the verdict of Supreme Court of the Republic Indonesia Number 1467 K/Pdt.Sus-PHI/2017)?. This research method is normative legal research using statue approach.